Influence of production-based biofuel and waste energy on environmental sustainability: Role of technological progress, economic growth and social globalization - Bilal Hussain; Zhao Rui Feng; Komal Batool; Ghadda Yousif; Syed Asif Ali Naqvi; Shafaqat Ali (Biomass and Bioenergy, 2026)

Corrigendum to ‘Carbon footprints and development: Unraveling the puzzle in belt and road economies’ [J. Environ. Manag. 394 (2025) 127582] - Bilal Hussain; Zhao Rui Feng; Komal Batool; Magdalena Radulescu; Daniel Balsalobre-Lorente (Journal of Environmental Management, 2026)

Edaravone dexborneol in acute ischemic stroke: a systematic review and meta-analysis of randomized trials with clinical and thrombectomy-specific subgroup analyses - Eman Tariq; Hooriya Ahmed; Tayyaba Ikram Qazi; Abdul Muhaimin; Aleena Amir Malik; Javeria Soomro; Rahimeen Qureshi; Zainab Murtaza; Sarum Ali Khan; Wajeeha Komal; Hadia Tanveer; Rida Ameer; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Carbon footprints and development: Unraveling the puzzle in belt and road economies - Bilal Hussain; Zhao Rui Feng; Komal Batool; Magdalena Radulescu; Daniel Balsalobre-Lorente (Journal of Environmental Management, 2025)

The effect of climate policy uncertainty and geopolitical risks on tourism development: a KRLS and frequency domain causality analysis - Bilal Hussain; Komal Batool; Syed Asif Ali Naqvi; Cosimo Magazzino (Environment, Development and Sustainability, 2025)
The tourism sector, indeed, is very delicate, and rising uncertainty can have a variety of effects. Geopolitical risks and climate policy uncertainty are resulting in unanticipated events that affect economic policy uncertainty. This study aims to investigate how climate policy uncertainty and geopolitical risks may affect tourism development in China. By using novel econometrics approaches, including the Dynamic Autoregressive Distributive Lags (ARDL) model, Kernel Regularized Least Squares (KRLS) method, and Frequency Domain Causality (FDC) test, the study’s findings demonstrate that geopolitical risk and climate policy uncertainty have negative long-term effects on tourism. However, economic sustainability, market volatility, financialization, and digitization have favorable effects on Chinese tourism. Moreover, the causality test results reveal that climate policy uncertainty causes tourism in the medium and short run. In contrast, geopolitical risks cause tourism in the long, medium, and short run. These results highlight that while performing risk analyses for tourism investment and policymaking, the Chinese government and practitioners working in the tourism industry should monitor both geopolitical risks and policy uncertainties related to the climate.

An effective bi-functional electrocatalyst for electrochemical water splitting using NiCo2O4 nanoparticles decorated with Polypyrrole nanocomposite - Khadija-Tul-Kubra; Faiqa Noreen; Ali Junaid; Atif Nazir; Sehrish Arshad; Komal Bibi; Ayesha Batool; Aleeza Sattar; Aboud Ahmed Awadh Bahajjaj; Sohail Ahmad; Muhammad Shuaib Khand; Syed Imran Abbas Shah (Fuel, 2025)

Spatio-temporal assessment of urban temperature variations and landscape characteristics using spectral indices - Hamza Shafiq; Riaz Ul Hissan; Ayesha Mariam; Shafaqat Ali; Abdelmohsen A. Nassani; Magdalena Radulescu; Komal Batool; Bilal Hussain (Gondwana Research, 2025)

Guar gum, Ulva lactuca L. biomass, and xanthan gum-based copolymer novel biosorbent for adsorptive removal of acid orange 10 - Samia Kanwal; Fozia Batool; Gulnaz Sharif; Hafiza Komal Naeem; Sobia Noreen; Humaira Yasmeen Gondal; Umar Bin Kamal; Allah Ditta (Biocatalysis and Agricultural Biotechnology, 2024)

Green synthesized silver nanoparticles: Characterization, phytostimulatory impacts, and degradation potential for organic pollutants - Ghania Abbas; Fozia Batool; Ambreen Ahmed; Shabana Wagi; Humaira Yasmeen Gondal; Farah Maqsood; Ehab A. Abdelrahman; Hafiza Komal Naeem; Samia Kanwal; Muhammad Mustaqeem; Allah Ditta (Biocatalysis and Agricultural Biotechnology, 2024)

Adsorption potential of orange rind–based nanosorbents for the removal of cadmium(II) and chromium(VI) from contaminated water - Samia Kanwal; Hafiza Komal Naeem; Fozia Batool; Awais Mirza; Ehab A. Abdelrahman; Gulnaz Sharif; Farah Maqsood; Muhammad Mustaqeem; Allah Ditta (Environmental Science and Pollution Research, 2023)